Efektivitas Perlindungan Sosial Masyarakat Melalui Program Keluarga Harapan (PKH) Terhadap Kesejahteraan Keluarga Penerima Manfaat (KPM) Di Era Pandemi Covid-19 (Studi Kasus Pada Kelurahan Koto Tangah Kota Payakumbuh) - Zamri, Khalid; Ariani, Ria (Jurnal Ekonomika Dan Bisnis (JEBS), 2022)
Poverty is a very complex and long-term problem. Therefore, how to reduce poverty also requires proper analysis. All components involved in the problem require appropriate solutions, sustainable, not temporary. This study aims to see the effect of the effectiveness of community social protection through the Family Hope program in reducing household poverty levels in the Covid-19 pandemic era in the Koto Tangah village on the welfare of the Beneficiary Family (KPM). The scope of this research problem is limited to indicators of effectiveness on the welfare of Beneficiary Families (KPM). This research is descriptive research. The method in this research uses mixed methods research which combines two approaches in research, namely qualitative and quantitative. The results in this study found that targeting accuracy, program socialization, and program objectives partially have a positive and significant effect on improving the welfare of the beneficiary community and have been very effective in social protection of the community. Meanwhile, for monitoring the PKH program, it has an effect but not significantly on improving people's welfare, but it is not significant because every thing is found when monitoring or evaluation must be followed up immediately.